Comparative Study of Continuous Versus Intermittent Subglottic Suction Drainage to Prevent Ventilator Associated Pneumonia in Intubated Patients - Bajracharya, Akriti; Rajbanshi, Lalit Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Subglottic secretion drainage reduces the incidence of ventilator associated pneumonia (VAP). The efficacy of Continuous subglottic secretion drainage (CSSD) over Intermittent subglottic secretion drainage (ISSD) for prevention of VAP is unknown. Objectives: Compare the efficacy of CSSD and ISSD in terms of incidence of VAP, mortality, duration of mechanical ventilation, length of ICU stay and incidence of reintubation. Methodology: This was a prospective comparative study conducted at Birat Medical College and Teaching Hospital. A total number of 80 intubated patients for at least 48 hours duration were included. Continuous and intermittent endotracheal suctioning techniques were compared for prevention of VAP and secondary outcomes in terms of length of mechanical ventilation, length of ICU stay, multiorgan failure, reintubation and mortality rate. Results: The incidence of VAP was 15% and 22.5 % in CSSD group while it was 17.5% and 27.5% in ISSD group in first 48 hours and 96 hours of mechanical ventilation respectively.The length of mechanical ventilation was significantly less in continuous group (4.78 ± 2.50 days) than in intermittent group (7.18 ± 2.09 days) with p value of 0.023. The patients with CSSD had significantly shorter ICU stay (5.49 ± 3.16 days) as compared to the patients with ISSD (8.46 ± 2.06 days). The incidence of reintubation was significantly higher in intermittent group patients (p value 0.024). Patients in both the group had comparable incidence of multiorgan failure, spontaneous breathing trial and mortality rate. Conclusion: The incidences of VAP and mortality were comparable in CSSD and ISSD. However CSSD significantly decreased the duration of mechanical ventilation, length of ICU stay and incidence of reintubation..